2004
DOI: 10.1002/art.20443
|View full text |Cite
|
Sign up to set email alerts
|

Association study of candidate genes for the prevalence and progression of knee osteoarthritis

Abstract: Objective. Osteoarthritis (OA), characterized by late-onset degeneration of articular cartilage, is recognized to have a genetic component. We examined the role of 26 single-nucleotide polymorphisms (SNPs) from 24 candidate genes in OA susceptibility and progression.Methods. We compared human complementary DNA libraries from OA-affected and normal cartilage and synovium and selected 22 genes in addition to the estrogen receptor ␣ and vitamin D receptor genes. Based on the availability of polymorphisms, we proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
146
1
5

Year Published

2006
2006
2011
2011

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 169 publications
(162 citation statements)
references
References 41 publications
10
146
1
5
Order By: Relevance
“…The association we observed was not particularly strong but was consistent with expression data comparing normal and OA-affected cartilage (20), the fact that serum levels of COMP are increased in OA (22), and the fact that COMP levels are heritable (34). A meta-analysis including both sets of data, however, showed no evidence of association between knee OA and COMP.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The association we observed was not particularly strong but was consistent with expression data comparing normal and OA-affected cartilage (20), the fact that serum levels of COMP are increased in OA (22), and the fact that COMP levels are heritable (34). A meta-analysis including both sets of data, however, showed no evidence of association between knee OA and COMP.…”
Section: Discussionsupporting
confidence: 80%
“…The cartilage oligomeric matrix protein gene (COMP) is a member of the thrombospondin gene family, which is known to be expressed more abundantly in OA cartilage than in normal cartilage (20). Prospective studies have shown that elevated serum levels of COMP are observed early in patients in whom chronic knee pain without radiographic OA progresses to radiographic disease (21).…”
mentioning
confidence: 99%
“…Moreover, we did not observe a sex-dependent allele frequency difference for the LRCH1 marker SNP, which suggests that some gene effects may be relevant for both sexes; this is consistent with the recent findings reported by Kizawa et al (16). It is also possible that this gene may influence the progression of disease as much as prevalent OA changes (36).…”
Section: Discussionmentioning
confidence: 99%
“…CILP-1 levels have been shown to increase with age (6, 10) and in patients with early stage osteoarthritis (11). The association of single nucleotide polymorphisms in the CILP1 gene with musculoskeletal disorders including osteoarthritis (12)(13)(14), and lumbar disc disease in a Japanese population (8) …”
mentioning
confidence: 99%